1993
DOI: 10.1039/dt9930000337
|View full text |Cite
|
Sign up to set email alerts
|

Addition of a carbonyl functionality to titanium carbenes. A study of the mechanism and intermediates in the Tebbe reaction

Abstract: The Tebbe transformation of carbonylic substrates such a s aldehydes, ketones, esters and amides into alkenes has been analysed theoretically. The active complex in the Tebbe reaction was modelled by various X,Ti=CH, (X = qS-CsH,, H or CI) complexes. The extended-Huckel approach was used to obtain a qualitative molecular orbital interaction picture of the reaction giving the expected titanaoxetane intermediate. A concerted path is proposed. A formally 2x + Zn reaction path is made allowed due t o the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The authors described the titanaoxetane as puckered with shortened Ti−C (2.074 Å) and elongated Ti−O (1.992 Å) bonds based on the crystal structure when compared to the complexes isolated by Beckhaus . The increased Ti−O bond length is in accordance with Jørgensen’s calculations of a weakening of that bond in the case of ring puckering . Classical Tebbe-like metathesis was not observed, but upon heating, the titanaoxetane slowly cyclometalated a Cp* methyl group under Ti−C bond cleavage and formed 121 .…”
Section: Isolated Metallaoxetanesmentioning
confidence: 73%
See 2 more Smart Citations
“…The authors described the titanaoxetane as puckered with shortened Ti−C (2.074 Å) and elongated Ti−O (1.992 Å) bonds based on the crystal structure when compared to the complexes isolated by Beckhaus . The increased Ti−O bond length is in accordance with Jørgensen’s calculations of a weakening of that bond in the case of ring puckering . Classical Tebbe-like metathesis was not observed, but upon heating, the titanaoxetane slowly cyclometalated a Cp* methyl group under Ti−C bond cleavage and formed 121 .…”
Section: Isolated Metallaoxetanesmentioning
confidence: 73%
“…Similar results had been published earlier by Schiøtt and Jørgensen based on frontier orbital interaction studies. In this study, it was also shown that the formally forbidden 2π + 2π cycloaddition could be made allowed by the involvement of a third high lying electron pair located on the methylene carbon atom . Böhme and Beckhaus also provided a theoretical explanation for the classical metathesis of titanaoxetanes to give a titanium oxide and an alkene or allene.…”
Section: Isolated Metallaoxetanesmentioning
confidence: 77%
See 1 more Smart Citation
“…The origin of the puckering of the TiOC 2 metallacycle ring is not obvious. A recent theoretical study concluded that a planar ground-state structure is more stable than a puckered one in molecules of the type X 2 TiOC(CH 2 )CH 2 ; puckering was found to weaken the Ti−O bond. It is noteworthy that, in the planar conformation, the calculations yield a Ti−C distance of 2.05 Å, very similar to the value found for 2 , 2.074(4) Å.…”
Section: Resultsmentioning
confidence: 99%
“…4 However, when the Tebbe reagent is treated with a Lewis base such as pyridine or THF, a highly reactive titanocene methylidene 2 is generated. This methylenates a range of carboxylic and carbonic acid derivatives, presumably via oxatitanacyclobutane 3, 5 to give alkenes 4 in a matter of minutes at room temperature and below. The reaction's driving force is probably the formation of the strong titanium oxygen double bond making it irreversible, 6,7 and this has prevented the development of a version that is catalytic in titanium.…”
Section: Tebbe Reagentmentioning
confidence: 99%